2022
DOI: 10.1186/s13039-022-00619-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a familial complex chromosomal rearrangement by optical genome mapping

Abstract: Background Complex chromosomal rearrangements (CCRs) are rare chromosomal structural variations, containing a variety of rearrangements such as translocation, inversion and/or insertion. With the development of cytogenetic and molecular genetic techniques, some chromosomal rearrangements that were initially considered to be simple reciprocal translocations in the past might eventually involve more complex chromosomal rearrangements. Case presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In contrast to these techniques, OGM has extremely high resolution and is capable of comprehensively detecting balanced and unbalanced SVs as small as 30 kb [ 17 ], which are unprecedented with karyotyping and CMA. For this reason, OGM has tremendous potential for the discovery of genetic causes of infertility, recurrent spontaneous abortion and histories of adverse pregnancy outcomes, as shown in this and other studies [ 7 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 79%
“…In contrast to these techniques, OGM has extremely high resolution and is capable of comprehensively detecting balanced and unbalanced SVs as small as 30 kb [ 17 ], which are unprecedented with karyotyping and CMA. For this reason, OGM has tremendous potential for the discovery of genetic causes of infertility, recurrent spontaneous abortion and histories of adverse pregnancy outcomes, as shown in this and other studies [ 7 , 8 , 16 ].…”
Section: Discussionmentioning
confidence: 79%
“…A vast majority of studies have demonstrated the utility of OGM in detecting nearly all types of chromosomal aberrations and highlighted its clinical superiority to SOC assays in detecting complex cryptic SVs. In assisted reproduction, OGM has been used to clarify the etiology of infertility, recurrent spontaneous abortion, and abnormal pregnancy histories ( Wang et al, 2020 ; Yang and Hao, 2022 ; Zhang et al, 2022 ). This technology not only helps optimize reproductive decisions but also avoids the birth of children with severe genetic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case for subchromosomal-size inversions for which OGM has been shown to be much more frequent than previously estimated ( Porubsky et al, 2022 ). OGM highlights that even copy-neutral insertions increase the burden of genetic disorders, demonstrating that some of them are found in regions refractory to sequencing ( Sabatella et al, 2021 ; Yang and Hao, 2022 ; Zhang et al, 2023 ). A separate condition concerns the so-called copy-neutral loss-of-heterozygosity (CN-LoH).…”
Section: Discussionmentioning
confidence: 99%